Intention and interpretation - Iseminger, Gary (Arts and their philosophies., 1992)
"" ... An excellent and comprehensive discussion of a debate that was initiated in this century in William Wimsatt's and Monroe C. Beardsley's influential article 'The Intentional Fallacy.' ... this is a splendidly conceived and very useful collection of essays. Readers will want to take issue with the arguments of individual authors, but this is to be expected in a volume at the cutting edge of a fertile philosophical controversy.""--David Novitz, The Philosophical Quarterly""What is the connection, if any, between the author's intentions in (while) writing a work of literature and the tr